Meio ambiente e igreja católica : o lugar das questões socioambientais nas campanhas da fraternidade de 1964 a 2020 - Santos, Marilia Barbosa dos (2022)
The object of study of this dissertation is the Fraternity Campaign (CF) and its relationship with socio-environmental issues. CF is an evangelizing service provided annually, since 1964, by the National Conference of Bishops of Brazil (CNBB). Its main objective is to awaken, in the churchgoers and in society, a solidary reflection/action on problems that affect Brazilian society (whether of social, political, economic or environmental nature). Analyzing, in the Brazilian context, the CF's carried out from 1964 to 2020 and based on the dimensions of sustainability proposed by Sachs (2008), this study had as a goal to understand how the Catholic Church approaches the socio-environmental issue. This way, we resorted to a dense socio-environmental documentary production prepared by the Catholic Church, as well as a vast literature based on Environmental Sciences and related areas. Content Analysis is the methodology used to understand the Church's approach to socio-environmental issues; it was possible to select, treat and interpret 34 (thirty-four) CF's, elected based on the dimensions of sustainability. The outcome of the analyzes indicated that the CF's, gradually, have sought to contextualize their discursive agendas to the Brazilian socio-environmental developments and have inserted, in a more active way, the ecclesial communities in decision-making, especially because these campaigns adhere to the ecumenical character. On account of this, this evangelizing service can be recognized as an instrument capable of supporting effective social participation in formative processes. However, the research highlighted the need for campaigns to consider the adhesion of Environmental Communication as a resource capable of guiding/narrowing the dialogues present in the CF's, as well as widening up their participation in the socio-environmental agendas that emerged in the spaces of social interaction. Faced with the social and environmental experiences analyzed with the CF's, it was possible to draw up the outline of an ecumenical pastoral plan whose objective is to present, to Churches linked to the National Council of Christian Churches in Brazil (CONIC), social and environmental practices based on the Sustainable Development Objectives (SDGs), aiming to intensify co-responsibility – individual and collective – regarding the local situation, in order to promote effective actions to mitigate social and environmental problems in collective spaces. To help the actions listed by the plan, Public Theology was presented as a possibility to strengthen the participation of member churches of CONIC in public decisionmaking, having as a perspective the consolidation of an effective integral socio-environmental praxis.